(untitled) (Scientific journal of the Fergana State University, 2023)
In order to improve the process of physical education, monitoring of the results of a study conducted by questionnaire methods is carried out on the implementation of various exercises related to athletics, the formation and development of their physical capabilities during the training sessions of a contingent of teachers. given in the article. The analysis of changes in indicators of the level of physical fitness and physical development of schoolchildren during the experiment is highlighted.